Maternal oral administration of osteocalcin protects offspring from metabolic impairment in adulthood. Issue 4 (4th March 2016) - Kawakubo‐Yasukochi, Tomoyo; Kondo, Akihiko; Mizokami, Akiko; Hayashi, Yoshikazu; Chishaki, Sakura; Nakamura, Seiji; Takeuchi, Hiroshi; Hirata, Masato
Abstract : Objective: Maternal diet during pregnancy has been found to influence the health of offspring. However, strategies for modulation of maternal energy metabolism without an adverse effect on the fetus have remained limited. It was recently shown that oral administration of uncarboxylated osteocalcin (GluOC) improves metabolic status in adult female mice. Whether maternal GluOC administration during gestation might improve the metabolic status of offspring was investigated. Methods: Female C57BL/6 mice were fed a normal diet (ND) or high‐fat, high‐sucrose diet (HFS) and were given saline or GluOC by oral administration during pregnancy. The resulting offspring were in turn assigned to ND‐ or HFS‐fed groups immediately after weaning, and their body weight, glucose metabolism, serum lipid parameters, and level of adipose tissue inflammation were subsequently assessed. Results: Maternal HFS feeding during gestation had adverse effects on glucose and lipid parameters, body weight, and adipose tissue inflammation in female offspring fed the same diet, and these effects were attenuated by maternal oral GluOC administration. Conclusions: Maternal oral administration of GluOC protects HFS‐fed female offspring from metabolic disorders induced by maternal obesity.